ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ПЕДАГОГІЧНОЇ ОСВІТИ ЯК НАЙВАЖЛИВІШИЙ ЧИННИК РОЗВИТКУ СУСПІЛЬСТВА (Педагогіка вищої та середньої школи, 2009)
The article deals with the problem concerning the ways of improvement pedagogical education effectiveness.